Design of Electronic Differential System for an Electric Vehicle with Four Independently Controlled In-Wheel PMSM - Yildirim, Merve; Oksuztepe, Eyyup; Kurum, Hasan (Univ Suceava, Fac Electrical Eng, 2024)
this study, a design of an Electronic Differential System (EDS) is presented for an Electric Vehicle (EV) with four independently controlled In-wheel Permanent Magnet Synchronous Motors (IW-PMSMs). To decrease the weight of the EV and eliminate the mechanical losses, an EDS is preferred instead of conventional mechanical differentials. In the literature, an EDS is commonly designed for only one pair of wheels. Conversely, in this study, an EDS for the four wheels of the EV is modeled and designed. Firstly, the speeds of four wheels are calculated by using the Ackermann-Jeantand geometry via Codesys software. Then, a dynamic model of the EV including all vehicle dynamics is created by MATLAB/Simulink. In the system, all sensors and IW-PMSMs are communicated by Controller Area Network-Bus (CANBus) which is commonly used in EVs due to its significant properties. Besides, a speed controller is designed to equal the EV speed taken from the real system to the reference speed. Finally, an experimental setup is established, and Codesys results are validated by both Simulink and experimental results. It is observed that safe driving of the EV with four IWPMSMs is provided by the designed system.
Keywords: electric vehicle; electronic differential system; in-wheel PMSM; dynamic model; CAN-Bus